1968
DOI: 10.1530/jrf.0.0170049
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of X-Irradiation of Rabbit Spermatozoa on Fertilization and Early Cleavage

Abstract: Summary. Exposure of rabbit semen to X-irradiation did not reduce the fertilization rate until doses of >25,000 r were used, although motility was noticeably affected at 15,000 r. Evidence of a depressant effect of much lower doses of X-irradiation on the fertilizing ability of rabbit spermatozoa was obtained, however, by using a more sensitive system in which irradiated aliquots from an ejaculate were inseminated mixed together with an exactly equivalent volume of untreated semen from the same ejaculate. Unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

1970
1970
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Following mixed insemination of equal volumes of X-irradiated and non-irradiated semen from 220 J. W. Overstreet and C. E. Adams the same ejaculate, Bedford & Hunter (1968) observed that the fertilizing ability of spermatozoa was not affected until doses of 15,000 R were adminis¬ tered. Determination of the source of the fertilizing spermatozoon was possible within only 48 to 50 hr following the ovulating injection since eggs fertilized by irradiated spermatozoa never cleaved more than twice whereas normally developing eggs had reached eight cells or more.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following mixed insemination of equal volumes of X-irradiated and non-irradiated semen from 220 J. W. Overstreet and C. E. Adams the same ejaculate, Bedford & Hunter (1968) observed that the fertilizing ability of spermatozoa was not affected until doses of 15,000 R were adminis¬ tered. Determination of the source of the fertilizing spermatozoon was possible within only 48 to 50 hr following the ovulating injection since eggs fertilized by irradiated spermatozoa never cleaved more than twice whereas normally developing eggs had reached eight cells or more.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of X-irradiation on rabbit spermatozoa have been studied on a number of occasions (Amoroso & Parkes, 1947; Chang, Hunt & Romanoff, 1957;Nuzhdin & Nizhnik, 1960;Bedford & Hunter, 1968). Following mixed insemination of equal volumes of X-irradiated and non-irradiated semen from 220 J. W. Overstreet and C. E. Adams the same ejaculate, Bedford & Hunter (1968) observed that the fertilizing ability of spermatozoa was not affected until doses of 15,000 R were adminis¬ tered.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Bedford & Hunter (1968) have reported that X-irradiation of rabbit spermatozoa at a dose level up to 10,000 rad has no effect on their fertilizing ability. Thus, when aliquots of spermatozoa irradiated at 10,000 rad were inseminated together with comparable aliquots of normal spermatozoa from the same ejaculate, the irradiated spermatozoa fertilized 50% of the ova.…”
Section: Introductionmentioning
confidence: 93%
“…In one series of experiments designed to study the effect of incubation at a slightly elevated temperature on the fertility of spermatozoa (Ulberg & Burfening, 1967), an ejaculate sample was incubated at 40°C for 3 hr, a control aliquot of the sample being incubated likewise at 38°C. The control or the experimental sample was then subjected to X-irradiation at a rate of 500 rad/ min, as described by Bedford & Hunter (1968), a total dose of 6000 to 7000 rad being given. The two equal volumes containing motile irradiated or nonirradiated spermatozoa in equal numbers were mixed thoroughly, and the mixture was inseminated intravaginally into an oestrous rabbit which also received an ovulating injection of 100 i.u.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation